The age of voltaire - Durant, Will, 1885-1981.; Durant, Ariel (Irvine, CA : World Library, 1996)
Unabridged digital version of the text of the same title. Features over 800 illustrations and maps, video documentary about the authors, and audio introductions to each volume.
1. Our oriental heritage -- 2. The life of Greece -- 3. Caesar and Christ -- 4. The age of faith -- 5. The Renaissance -- 6. The Reformation -- 7. The age of reason begins -- 8. The age of Louis XIV -- 9. The age of Voltaire -- 10. Rousseau and revolution -- 11. The age of Napoleon.
Title from disc label.
System requirements for DOS: IBM-compatible PC; 640KB RAM; DOS 3.3 or higher; VGA monitor; hard disk; CD-ROM drive. Sound Blaster card required for audio.
System requirements for Windows: 386 IBM PC or compatible; 2MB RAM; Windows 3.1 or higher; VGA monitor; CD-ROM drive. Sound Blaster-compatible audio card, 16-bit video card, and MPC-rated CD-ROM drive (150KB per second or faster) required to play video.
Keywords: Civilization -- History